Human herpesviruses in the pathogenesis of orbit and eye tumors: detection of herpesvirus DNA in tumor biopsies - A. E. Andryushin; I. P. Khoroshilova; G. P. Zakharova; A. M. Maybogin; A. V. Trukhina; A. E. Andryushin; I. P. Khoroshilova; G. P. Zakharova; A. M. Maybogin; A. V. Trukhina (Российский офтальмологический журнал, 2018)
Biopsy samples of 32 patients with uveal melanoma (10), RBL (11), orbital lymphoma (7), lacrimal gland adenomas (2), rhabdomyosarcoma of conjunctiva (2) were tested by real time polymerase chain reaction (PCR) to detect the DNA of HSV 1, HSV 2, EBV, CMV, HHV-6, HHV-8, Toxoplasma gondii, Mycoplasma hominis, Ureaplasma spp. Totally, 14 of 32 (43.75 %) tumor samples revealed DNA herpesviruses, Chlamydia trachomatis, mycoplasma hominis or ureaplasma spp. Positive PCR results were revealed in orbital lymphoma almost 2 times more frequently than in RBL (6/7 - 85.7 % and 5/11 - 45.5 %; p = 0.15), and 4 times more frequently than in uveal melanoma (6/7 - 85.7 % and 2/10 - 20%; р = 0.015). The spectrum of pathogens in different tumors varied. Only genomes of lymphotropic HHV (EBV, HHV-6, HHV-8) with predominance of EBV are found in orbital lymphoma. In RBL, we could identify DNA of HHV 6, EBV, CMV, and ureaplasma. Infectious DNA were detected the least frequently (2 out of 10 patients) in biopsies of uveal melanoma: in both cases, Chlamydia trachomatis genome was found, in one of them it combined with EBV and CMV DNA. Plasma investigation revealed positive PCR results significantly less frequently than in biopsies (1/28 and 14/32; p = 0.002). Further studies are needed to assess the role of persistent pathogens, primarily human herpesviruses, Chlamydia and ureaplasma in the pathogenesis of orbit and eye tumors // Russian Ophthalmological Journal, 2016; 2: 42-46 . doi: 10.21516/2072-0076-2016-9-2-42-46 .